2002
DOI: 10.1103/physrevb.66.165319
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of Ca/Si(111) surfaces

Abstract: The surface structures of different Ca/Si͑111͒ surfaces were studied by low-energy electron diffraction ͑LEED͒ and high-resolution core-level photoelectron spectroscopy. Five different phases were observed in LEED depending on the Ca coverage. The lowest coverage phase has both (3ϫ2) and c(6ϫ2) periodicities, and the highest coverage phase has a (2ϫ1) periodicity. The LEED patterns of the three intermediate phases were (5ϫ2), (7ϫ1), and (9ϫ1). In the Si 2p core-level spectra, three surface components were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 27 publications
(57 reference statements)
7
54
2
Order By: Relevance
“…The negligible correlation between the -bond state and the adsorbate is confirmed by the fact that this state is observed in the same binding energy range ͑1.5-2.5 eV͒ as similar dispersion in previous studies performed on monovalent 6,26 -29 and divalent 7,15,18,19 atom induced Si͑111͒-(3ϫ1) and (3ϫ2) HCC surfaces. Therefore, since ͑1͒ the basic structure of the Ca/Si͑111͒-(3ϫ2) surface is the same as the HCC structure of the Li/Si͑111͒-(3ϫ1) surface, [17][18][19] ͑2͒ the dispersion of S 3 shows good agreement with that of S 1 ϩ at k // larger than 0.9 Å Ϫ1 , and ͑3͒ the S 3 state is observed in a binding energy range of 1.5-2.5 eV, we conclude that the origin of S 3 is the -bond state between the C and D Si atoms displayed in Fig. 1͑b͒.…”
Section: Fig 2 Leed Patterns Of the Ca/si͑111͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The negligible correlation between the -bond state and the adsorbate is confirmed by the fact that this state is observed in the same binding energy range ͑1.5-2.5 eV͒ as similar dispersion in previous studies performed on monovalent 6,26 -29 and divalent 7,15,18,19 atom induced Si͑111͒-(3ϫ1) and (3ϫ2) HCC surfaces. Therefore, since ͑1͒ the basic structure of the Ca/Si͑111͒-(3ϫ2) surface is the same as the HCC structure of the Li/Si͑111͒-(3ϫ1) surface, [17][18][19] ͑2͒ the dispersion of S 3 shows good agreement with that of S 1 ϩ at k // larger than 0.9 Å Ϫ1 , and ͑3͒ the S 3 state is observed in a binding energy range of 1.5-2.5 eV, we conclude that the origin of S 3 is the -bond state between the C and D Si atoms displayed in Fig. 1͑b͒.…”
Section: Fig 2 Leed Patterns Of the Ca/si͑111͒mentioning
confidence: 99%
“…Among the other AEM induced (3ϫ2) surfaces, the Ca/Si͑111͒-(3ϫ2) surface was reported to have the same geometric structure as the Ba induced surface. [17][18][19] So far, three studies have reported the electronic structure of this surface, and a basic understanding is important in order to obtain a complete comprehension of the metal atom induced HCC structure. 8,18,19 However, these studies cover only a part of the surface Brillouin zone ͑SBZ͒, and the results are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of Si(111)-(3×1) surface has been reported to be formed by various adsorbates, e.g., alkali metals (AM's), alkaline-earth metals (AEM's), rare-earth metals (Eu, Sm and Yb), and Ag with a coverage of either 1/3 monolayer (ML) or 1/6 ML. Although some of the adsorbates actually show different diffraction patterns (Ag shows a (6×1) pattern [3][4][5][6], and Ca [7,8], Eu and Yb [9,10] show a (3×2) pattern) all reconstructed surfaces are widely believed to have a quite similar structure based on the similarity of the low-energy electron diffraction (LEED) I-V curves [11,12], scanning-tunnelingmicroscopy (STM) images [13][14][15][16][17], and surface core-level shift measurements [3,8,[17][18][19][20]. That is, the basic structures of all these surfaces follow the honeycomb-chainchannel (HCC) model [21][22][23], which was originally proposed for 1/3 ML monovalent atom induced Si(111)-(3×1) reconstructions, and the difference in diffraction pattern is proposed to originate from the different adsorption sites of the metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Ca induced Si(111)-(3×2) HCC surface, only weak ×2 streaks were observed in low-energy electron diffraction (LEED) at 300 K, while ×2 spots were observed at 100 K [7,8,25,26]. Taking into account that the surface energy for H 3 site adsorption ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation